Penerapan Model Discovery Learning Untuk Meningkatkan Keaktifan Belajar Siswa Saat Pandemi - Yoga Handita Handita; Puguh Wahyu Prasetyo; Sugiyem Sugiyem (Pendidikan Matematika Universitas PGRI Yogyakarta, 2022)
The education sector is feeling the impact of the COVID-19 pandemic. During the pandemic, the procedure for teaching and learning activities (TLA) changes according to the circumstances, this greatly affects the level of student learning activity (SLA). The purpose of this study is to improve SLA using the discovery learning mode (DLM) which is accompanied by the TPACK approach in mathematics teaching and learning. The type of research used is classroom action research (CAR), in this CAR it uses two cycles and each cycle has two meetings. This PTK takes the research subject, namely students of class X MIPA 2 SMAN 1 Bantul in the even semester of the 2021/2022 academic year. The results of this CAR show that there is an increase in SLA in mathematics learning using MDL. The increase in the SLA value can be seen from the pre-cycle results with the percentage value of 62.8% increasing to 71.42% after going through the action during the first cycle, then during the second cycle there was an increase with the percentage value of 89.7%. In cycle II, all SLA indicators have reached the desired criteria. The desired SLA criteria are with a minimum score percentage of 75% with high criteria.Keywords: discovery learning, Classroom Action Research, Student Learning Activity